2010
DOI: 10.1590/s0074-02762010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new phlebotomine species, Martinsmyia reginae sp. nov. (Diptera: Psychodidae: Phlebotominae) from a cave in the state of Tocantins Brazil

Abstract: Phlebotomines are invertebrate hosts of Leishmania species, which cause leishmaniases and are responsible for the transmission of Leishmania to humans and other mammals. They are also the vectors of arboviruses and the causative agents of bartonellosis and their bites cause allergic reactions (Young & Duncan 1994). Caves are ecotopes that are significantly different from their external surrounding environments and sand flies are constantly found among the insects that live in caves or visit their surrounding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Initial studies of phlebotomine fauna in TO focused on the description of species (Barreto 1946, Martins et al 1962, 1964, 1975); further entomological studies identified 32 sandfly species in the state (Lustosa et al 1968, Andrade Filho et al 2001), including the new species Micropygomyia (Silvamyia) echinatopharynx and Martinsmyia reginae (Andrade Filho et al 2004, Carvalho et al 2010). These findings indicate a great diversity of sandfly species in TO.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of phlebotomine fauna in TO focused on the description of species (Barreto 1946, Martins et al 1962, 1964, 1975); further entomological studies identified 32 sandfly species in the state (Lustosa et al 1968, Andrade Filho et al 2001), including the new species Micropygomyia (Silvamyia) echinatopharynx and Martinsmyia reginae (Andrade Filho et al 2004, Carvalho et al 2010). These findings indicate a great diversity of sandfly species in TO.…”
Section: Discussionmentioning
confidence: 99%
“…Alves et al (2008) described Lutzomyia maruaga, which was captured in the aphotic zone of a sandstone cave in AM. Carvalho et al (2010) described Martinsmyia reginae, captured in a cave in the state of Tocantins, and Carvalho et al (2011a) described Evandromyia spelunca, found in a cave in Lassance, MG. In the present study, an undescribed species (Lutzomyia sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new species of sandfly, Lutzomyia maruaga (Alves, Freitas & Barret 2008) was found in a cave in the Amazon region, which shows that it is at least facultatively parthenogenetic and autogenic, as previously observed for Lutzomyia mamedei by Brazil and Oliveira [20], and therefore regarded as a kind of troglobite. Other studies have also described new species of sandflies reported from cave environments [8], [9]. Evandromyia spelunca is a new phlebotomine species of the cortelezzii complex described from this cave [9].…”
Section: Discussionmentioning
confidence: 76%
“…The number of sandflies found is increasing rapidly, with descriptions of new species every year, including species associated with caves [7], [8], [9]. However, with regard to biology, there is still a large gap in the understanding of these insects.…”
Section: Introductionmentioning
confidence: 99%